Dutch ministry of Agriculture, Nature and Food Quality is stimulating circularity (including reducing FLW, reducing GHG emissions) through new platform - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Based on diverse inputs from WUR, including on FLW and associated GHG emissions, the Dutch government has formulated visions for sustainable development, and implemented a 'Taskforce Circular Economy in Food' (in Dutch: "Samen tegen voedselverspilling") in which leading industries, retailing organizations, governmental bodies and science groups co-operate to identify and implement "circular" innovations.